2022
DOI: 10.3390/su14031544
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of New Spaces for Threatened Mammals: Assessing Habitat Suitability for Kashmir Markhor (Capra falconeri cashmeriensis) in the Hindukush Range

Abstract: Natural wild habitats are either destroyed or shrunk due to human interventions. Therefore, habitat evaluation is crucial for managing wildlife populations and designing robust conservation strategies. Species presence data and geographic information system (GIS) coupled with ground-breaking powerful statistical techniques have made such assessments possible. We used maximum entropy modeling (MaxEnt) to identify suitable habitats for Kashmir markhor (Capra falconeri cashmeriensis) in Malakand Division, Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A threshold value (r ≥ ±0.8) was used to further reduce the number of variables. Any two variables with an r value above the selected threshold were targeted, and those contributing less were omitted [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…A threshold value (r ≥ ±0.8) was used to further reduce the number of variables. Any two variables with an r value above the selected threshold were targeted, and those contributing less were omitted [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although there are numerous reports that the landscape genetic approach adopted in this study is beneficial for wild animal management and conservation of native ecosystems (Franz et al, 2012; Sacks et al, 2016; Dellicour et al, 2019; Epps et al, 2019; Ohnishi et al, 2019; Rutten et al, 2019; Khattak et al, 2022), in this study, we were able to comprehensively evaluate multiple landscape elements at the individual level. This study also showed that landscape elements, such as topography and weather, influence the occurrence and dispersal of Japanese wild boars.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, attention has been paid to the relationship between genetic and geographic distances of target organisms between regions (isolation by distance) or between genetic distances and resistance (isolation by resistance) in an attempt to identify factors that hinder gene flow among populations (Manel et al, 2003; Holderregger and Wangner, 2008). Mammalian species for which landscape genetic analyses have been undertaken include red fox ( Vulpes vulpes ; Sacks et al, 2016), red deer ( Cervus elaphus ; Dellicour et al, 2019), American beaver ( Castor canadensis ; Epps et al, 2019), Asian black bear ( Ursus thibetanus ; Ohnishi et al, 2019), Kashmir markhor ( Capra falconeri cashmeriensis ; Khattak et al, 2022), and wild boars ( Sus scrofa ), mainly in Europe (Franz et al, 2012; Dellicour et al, 2019; Rutten et al, 2019). Most conventional landscape genetic analyses have been conducted at the population level, but the importance of individual-based approaches with specific coordinates of sample locations has been emphasized, especially in the central Japanese archipelago, which has a complex topography within a small area, including narrow plains and high mountains.…”
Section: Introductionmentioning
confidence: 99%
“…Pearson correlation matrix was used in program R (version 3.6.2) to remove highly correlated variables from the analysis (Welch et al, 1994). After this procedure, ten variables were retained (r < 0.7) (Khattak et al, 2022).…”
Section: Selection Of Presence Data and Environmental Variablesmentioning
confidence: 99%
“…According to Johnson (1980), mobile animal species make excursions in search of areas comprising all the resources essential for reproduction and survival all year round referred to as habitat selection. However, anthropogenic activities have largely demolished these natural wild habitats bringing many species to extinction (Khattak et al, 2022). Such disturbing effects of human activities have alarmed scientists to safeguard the species by preserving their habitats (Suel, 2019).…”
Section: Introductionmentioning
confidence: 99%